Berberine Attenuates Intestinal Mucosal Barrier Dysfunction in Type 2 Diabetic Rats - Gong, Jing; Hu, Meilin; Huang, Zhaoyi; Fang, Ke; Wang, Dingkun; Chen, Qingjie; Li, Jingbin; Yang, Desen; Zou, Xin; Xu, Lijun; Wang, Kaifu; Dong, Hui; et al. (Frontiers in Pharmacology, 2017)
Backgroud: Intestinal mucosal barrier dysfunction plays an important role in the development of diabetes mellitus (DM). Berberine (BBR), a kind of isoquinoline alkaloid, is widely known to be effective for both DM and diarrhea. Here, we explored whether the anti-diabetic effect of BBR was related to the intestine mucosal barrier. Methods and results: The rat model of T2DM was established by high glucose and fat diet feeding and intravenous injection of streptozocin. Then, those diabetic rats were treated with BBR at different concentrations for 9 weeks. The results showed, in addition to hyperglycemia and hyperlipidemia, diabetic rats were also characterized by proinflammatory intestinal changes, altered gut-derived hormones, and 2.77-fold increase in intestinal permeability. However, the treatment with BBR significantly reversed the above changes in diabetic rats, presenting as the improvement of the high glucose and triglyceride levels, the relief of the inflammatory changes of intestinal immune system, and the attenuation of the intestinal barrier damage. BBR treatment at a high concentration also decreased the intestinal permeability by 27.5% in diabetic rats. Furthermore, BBR regulated the expressions of the molecules involved in TLR4/MyD88/NF-кB signaling pathways in intestinal tissue of diabetic rats. Conclusion: The hypoglycemic effects of BBR might be related to the improvement in gut-derived hormones and the attenuation of intestinal mucosal mechanic and immune barrier damages.